Screening of Pear Germplasm against Entomosporium leaf and fruit spot disease - Z.A. BHAT, S. ALTAF, T.R. RATHER*, N.A. KHAN and (Indian Phytopathology, 2017)
Fourteen pear varieties were screened under polyhouse conditions for their tolerance/susceptibility against the pathogen. One year old healthy grafted plants of fourteen pear varieties were planted in 50 cm diameter plastic pots containing sterilized soil and were kept under polyhouse conditions equipped with sprinkler irrigation facility. The results revealed that only one cultivar i.e. Starkrimson exhibited immune reaction and six other cultivars viz., Fertility, Beurré hardy, Beurré Clairgeau, Clapp’s favorite, Citron-Des-Carmes, and Max Red Bartlett were rated as moderately susceptible. The remaining cultivars viz., Chinese sandy pear, Conference, Cosia C, Cosia F, Bartlett, Red Anjou and Beurré-DeAmanalis exhibited highly susceptible reaction.